Dithiocarbazate Ligand-Based Cu(II), Ni(II), and Zn(II) Complexes: Synthesis, Structural Investigations, Cytotoxicity, DNA Binding, and Molecular Docking Studies - Enis Nadia Md Yusof; Mohammad Azam; Siti Syaida Sirat; Thahira B. S. A. Ravoof; Alister J. Page; Abhi Veerakumarasivam; Thiruventhan Karunakaran; Mohd Rizal Razali (Bioinorganic Chemistry and Applications)
S-4-methylbenzyl-β-N-(2-methoxybenzylmethylene)dithiocarbazate ligand, 1, prepared from S-(4-methylbenzyl)dithiocarbazate, was used to produce a novel series of transition metal complexes of the type, [M (L)2] [M = Cu(II) (2), Ni(II) (3), and Zn(II) (4), L = 1]. The ligand and its complexes were investigated by elemental analysis, FTIR, 1H and 13C-NMR, MS spectrometry, and molar conductivity. In addition, single X-ray crystallography was also performed for ligand, 1, and complex 3. The Hirshfeld surface analyses were also performed to know about various bonding interactions in the ligand, 1, and complex 3. The investigated compounds were also tested to evaluate their cytotoxic behaviour. However, complex 2 showed promising results against MCF-7 and MDA-MB-213 cancer cell lines. Furthermore, the interaction of CT-DNA with ligand, 1, and complex 2 was also studied using the electronic absorption method, revealing that the compounds have potential DNA-binding ability via hydrogen bonding and hydrophobic and van der Waals interactions. A molecular docking study of complex 2 was also carried out, which revealed that free binding free energy value was −7.39 kcal mol−1.